(untitled) (Praxis Educativa, 2022)
Museums are educational contexts where people develop different types of experiences. A study is presented that tries to understand, from different perspectives, the experiences of young people in museums. 89 young people, located in the age group of 13 to 22 years, from different localities of Argentina (Río Cuarto, Las Higueras, Córdoba Capital, La Pampa and San Luis) and from different educational institutions (state-managed and private). In addition, three museum educators were interviewed; the first one has a degree in Initial Education, she works in the Regional Historical Museum of Río Cuarto as the person in charge of the Educational Extension Area. The second one has a degree in Art, she is in charge of the guided visits in the Museum of the National University of Tucumán; and the third works as a non-teacher in the Education Area of the Museum of Anthropology, of the National University of Córdoba. Semi-structured interviews conducted by video calls to museum educators and online questionnaires for young people were used for data collection, since the process was carried out during the pandemic context. The data analysis was performed based on constant comparisons and open and selective coding. The results indicate that some young people perceive museums as foreign, boring and unmotivating spaces, however, they identify some educational potential of these contexts. The analyzes highlight that the young public needs to participate in interactive proposals that favor social exchange and challenge their creativity. It will be necessary to work on the design of diverse, situated and contextualized strategies for young people. Keywords: youth; museums; education; creativity; study of the public